2020
DOI: 10.1158/1078-0432.ccr-20-0566
|View full text |Cite
|
Sign up to set email alerts
|

Genome Instability Profiles Predict Disease Outcome in a Cohort of 4,003 Patients with Breast Cancer

Abstract: ◥Purpose: The choice of therapy for patients with breast cancer is often based on clinicopathologic parameters, hormone receptor status, and HER2 amplification. To improve individual prognostication and tailored treatment decisions, we combined clinicopathologic prognostic data with genome instabilty profiles established by quantitative measurements of the DNA content.Experimental Design: We retrospectively assessed clinical data of 4,003 patients with breast cancer with a minimum postoperative follow-up perio… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…17,52 This observation, however, is not universally applicable, and the complex biology of breast cancer in young women, with its potentially aggressive features, remains poorly understood. 53 This study addressed the variability in disease outcome by selecting younger breast cancer patients with short and long survival (mean DSS, <4 versus >19 years) from over 5000 cases treated in the greater Stockholm area between 1986 and 2001. The potential genetic basis of the disparate outcome was explored by determining the genetic instability profile using miFISH, which allows for the enumeration of copy numbers of cancer genes in individual cells across the tumor cell population and an assessment of the degree of ITH.…”
Section: Discussionmentioning
confidence: 99%
“…17,52 This observation, however, is not universally applicable, and the complex biology of breast cancer in young women, with its potentially aggressive features, remains poorly understood. 53 This study addressed the variability in disease outcome by selecting younger breast cancer patients with short and long survival (mean DSS, <4 versus >19 years) from over 5000 cases treated in the greater Stockholm area between 1986 and 2001. The potential genetic basis of the disparate outcome was explored by determining the genetic instability profile using miFISH, which allows for the enumeration of copy numbers of cancer genes in individual cells across the tumor cell population and an assessment of the degree of ITH.…”
Section: Discussionmentioning
confidence: 99%
“…In recent decades, genomic instability has risen as a predictor of cancer outcomes and offers opportunity for targeted treatment. In a large cohort of breast cancer patients, genome instability profiles were found to predict mortality outcomes independent of clinicopathological parameters [ 1 ]. A number of breast cancer predisposition genes ( ATM, BRCA1, BRCA2, CHEK2, TP53, and PALB2 ) are important gatekeepers to maintaining DNA replication fidelity by regulating DNA damage repair.…”
Section: Introductionmentioning
confidence: 99%
“…Genomic instability often relates to tumor-prone phenotypes and required for the acquisition of tumor-initiating mutations [ 5 ]. More importantly, many researchers indicated that genomic instability accumulation refers to patients' tumor progression and prognosis [ 6 , 7 ]. Even though genomic instability mechanisms have not been wholly discovered, abnormal epigenetics has been reported related to genomic instability [ 8 ], indicating molecular signature's capability as a quantitative analysis for genomic instability.…”
Section: Introductionmentioning
confidence: 99%